(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This study examines the methodological foundations for organizing investment activity under alternative financing conditions and analyzes their development trends in the context of modern economic transformations. The research highlights the growing importance of alternative financing instruments—such as crowdfunding, venture capital, peer-to-peer lending, and private equity—in enhancing access to capital and improving investment efficiency. The paper explores key theoretical approaches, including financial intermediation, financial innovation, and institutional frameworks, and links them with practical applications in contemporary financial systems. Additionally, the study provides a comparative analysis of alternative financing mechanisms and identifies their advantages, limitations, and impact on investment processes. The findings indicate that diversification of financing sources, integration of financial technologies, and the development of appropriate methodological approaches play a crucial role in ensuring sustainable investment activity. The paper concludes by emphasizing the need for continuous improvement of methodological frameworks to adapt to the evolving landscape of alternative finance.